Sistem Informasi Tugas Akhir Mahasiswa pada Program Studi STMIK Palangkaraya Berbasis Web Mobile - Susi Hendartie (Jurnal Sains Komputer dan Teknologi Informasi, 2019)
Information systems and computer technology was developing rapidly because for information needed. The development of information technology. Could not separated from develop of computer technology, because computer was a media that could make easy to finish their work. The Change and dynamics of society’s grown rapidly with developmen of information technology that requires effective and efficient in terms of time. One of them helped in the process of final exam. The writer interest to make an information system based on mobile web that can solve the problem. The system will make based on object with the title make a data of final exam information system in Faculty of STMIK Palangkaraya based on mobile web. The results of this study are expected by the online aplication Final exam in faculty of STMIK Palangkaraya final and students to sign the final task quikly and accurately to assisted help faculty STMIK of Palangkaraya to collected a data of final exam and for student to sign. Final exam Seminar proposal, Final task quikkly and accurately. The collection of data by used this aplication also does not consume a lot of time and money because it can reach Final registration which is outside the city, outside the island even residing outside the country though.